Geographies of wellbeing and chronic illness: A Canadian case study - Cardwell, Francesca S.; Elliott, Susan J.; Barber, Megan R. W.; Cheema, Kim; Boucher, Adrian; Clarke, Ann E. (The Canadian geographer, 2025)
Geography has had a long legacy of research investigating the lived experiences of individuals with chronic illness, particularly women. Health geographers have also begun to focus beyond health to wellbeing, defined as that space between expectation and reality. Individuals living with chronic illness often experience complex impacts to their lifestyle, relationships, aspirations, and employment that affect this space, expressed as emotional, mental, and psychosocial health and wellbeing impacts. Systemic lupus erythematosus (SLE) is a chronic autoimmune condition disproportionately affecting women. Lupus nephritis (LN) is a manifestation of SLE that affects the kidneys, developing in up to 60% of those with SLE. Impacts extend beyond the physiological, as LN affects capacity to conceive and carry a child. Individuals aged ≥18 years with LN were recruited from a Canadian lupus cohort to participate in semi‐structured in‐depth interviews (n = 30). At the individual level, participants reported emotional impacts experienced at LN diagnosis (e.g., uncertainty, fear, surprise, relief) and in daily life (e.g., fear of future, stigmatization). At the meso level, participants shared how relationships (e.g., feeling supported, treated differently), leisure activities (e.g., modifying activities), paid employment and education (e.g., altered career paths), and family planning (e.g., conception challenges) impacted wellbeing. Results increase our understanding of how living with chronic illness impacts wellbeing and can inform policy and practice change. La géographie a une longue tradition de recherche sur le vécu des personnes atteintes de maladies chroniques, en particulier les femmes. Les géographes de la santé ont commencé à s’intéresser également au bien‐être, défini comme l’écart entre les attentes et la réalité. Les personnes atteintes de maladies chroniques ressentent souvent des impacts complexes sur leur mode de vie, ce qui affecte cet écart et se traduit par des impacts sur leur santé mentale ainsi que sur leur bien‐être. Le lupus érythémateux disséminé (LED) est une maladie auto‐immune chronique qui touche particulièrement les femmes. La néphrite lupique (NL) est une manifestation du LED qui affecte les reins et se développe chez jusqu’à 60 % des personnes atteintes de LED. La NL affecte notamment la capacité à concevoir et à porter un enfant. Des personnes âgées de ≥ 18 ans atteintes de NL ont été recrutées dans une cohorte canadienne pour participer à des entretiens semi‐structurés approfondis (n = 30). Au niveau individuel, les participants ont rapporté les émotions ressenties au moment du diagnostic de la NL (p. ex., incertitude, peur, surprise, soulagement) et dans leur vie quotidienne (p. ex., peur de l’avenir, stigmatisation). Au niveau méso, les participants ont expliqué comment les relations (p. ex., le sentiment d’être soutenu ou traité différemment), les loisirs (p. ex., la modification des activités), l’emploi rémunéré et l’éducation (p. ex., les changements de carrière) et la planification familiale (p. ex., les difficultés à concevoir) ont eu un impact sur leur bien‐être. Les résultats renforcent notre compréhension de l’impact d’une maladie chronique sur le bien‐être et ceux‐ci peuvent éclairer les changements de politiques et de pratiques. Individuals with lupus nephritis, a chronic autoimmune disease affecting the kidneys, experience substantial impacts to wellbeing. Participants report individual and meso level factors that contribute to how lupus nephritis is experienced at diagnosis and in daily life. While macro level factors were not discussed, interventions that influence wellbeing should be considered at the system level.